A review of Cayley graph properties and expander family - Cortes Garcia, Christian Camilo (2020)
In this paper some concepts used in graph theory are introduced, such as directed, undirected, connected, tree, regular or gradient, divergent or Laplacian graphs, and relationships between the diameter of the graph, or the largest second proper value of its adjacency matrix, with respect to the Cheeger constant to identify expander graphs k-regular. With these guidelines defined, some properties are introduced in Cayley graphs, with illustrative examples, and methodologies to identify if the corresponding graph is k-regular or a directed tree. Finally, Cayley expander graphs are related to their diameter or the second largest eigenvalue.